The Relation of Violent Video Games to Adolescent Aggression: An Examination of Moderated Mediation Effect - Shao, Rong; Wang, Yunqiang (Frontiers in Psychology, 2019)
To assess the moderated mediation effect of family environment and normative beliefs regarding aggression upon exposure to violent video games and adolescent aggression. The subjects self-reported their exposure to violent video games, family environment, normative beliefs about aggression, and aggressive behavior. The results showed a significant positive correlation between exposure to violent video games and adolescent aggression; normative beliefs about aggression had a mediation effect on exposure to violent video games and adolescent aggression, while family environment moderated the first part of the mediation process. For individuals with a good family environment, exposure to violent video games had only a direct effect on aggression; however, for those with poor family environment, it had both direct and indirect effects mediated by normative beliefs about aggression. This moderated mediation model includes notions of the General Aggression Model and Catalyst Model, which helps shed light on the complex mechanism of violent video games influencing adolescent aggression.